Analisis Sosiologi Sastra dalam Antalogi Dengung Tanah Goyah Karya Iyut Fitra: A Sociological Analysis of Literature in Iyut Fitra’s Poetry Anthology Dengung Tanah Goyah - Putri Delia; Inggri Selpi Arianti; Salwa Salwa; Dela Tika; Elmustian Elmustian (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to examine social and spiritual values in the poems of Iyut Fitra through the sociological approach to literature. Using a descriptive qualitative method and content analysis, fifteen poems were analyzed based on thematic relevance and symbolic strength. The findings reveal four main patterns: social patriotic, narrative social, realist social critique, and reflective religious. These patterns represent the poet’s ideological journey from collective social struggle to profound spiritual reflection. The results indicate that Iyut Fitra’s poetry functions not only as an aesthetic expression but also as a medium for social, moral, and spiritual reflection, emphasizing the poet’s moral responsibility toward humanity. Thus, his works serve as both a mirror of social reality and a vehicle for moral and spiritual awareness.